PHYTOCHEMICAL ANALYSIS AND IN VITRO ANTIOXIDANT ACTIVITY OF A WILD EDIBLE MUSHROOM ENTOLOMA LIVIDOALBUM - Dasgupta, Adhiraj; Rai, Manjula; Acharya, Krishnendu (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: In the course of inventorying and bioprospecting wild edible mushrooms of West Bengal, the ethanolic fraction of Entoloma lividoalbum was tested for its potential as an antioxidant in vitro and estimate the amounts of putative bioactive compounds present in it. Methods: The fraction's antioxidant potential was tested by employing various in vitro assay systems, namely, total antioxidant capacity, chelating effect on ferrous ions, reducing the effect of ferric iron and 1,1-diphenyl-1-picrylhydrazyl radical scavenging assays. Estimation of bioactive components was carried out following previously established methods. Results: It was found to be a great reducer of ferric iron, as well as an effective ferrous iron chelator and free radical scavenger. In an attempt to quantify the bioactive components, the fraction was found to be comprised of mention worthy amounts of phenols, Î²-carotene, lycopene and flavonoids. Conclusion: This fraction can be used to treat oxidative stress related ailments. Keywords: Antioxidant, 1,1-diphenyl-1-picrylhydrazyl, Reducing power, Scavenging activity.